2022
DOI: 10.1111/codi.16088
|View full text |Cite
|
Sign up to set email alerts
|

Robotic abdominal resection of tailgut cysts – A technical note with step‐by‐step description

Abstract: Aim Here, we describe a step‐by‐step standardized technique for tailgut cyst resection using a single‐docking robotic approach. Method Each step of the technique is illustrated using a composite collection of four operative patient videos to demonstrate the advantages and feasibility of this technique. The robot platform utilised is Da Vinci Xi. Results Five female patients have undergone this operation in our unit. The size of tumours ranged from 12 to 45 mm. Median operating time was 100 min (range 90–150). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The existence of a multilocular cyst, which is usually filled with mucoid content, is a useful diagnostic criterion for tailgut cyst (1). The management of tailgut cyst comprises complete surgical resection-either open, laparoscopic or robot-assisted surgery (1,(6)(7)(8). The appropriate surgical approach depends on the location and size of the lesion, and its relation with the surrounding structures (1,6,7).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a multilocular cyst, which is usually filled with mucoid content, is a useful diagnostic criterion for tailgut cyst (1). The management of tailgut cyst comprises complete surgical resection-either open, laparoscopic or robot-assisted surgery (1,(6)(7)(8). The appropriate surgical approach depends on the location and size of the lesion, and its relation with the surrounding structures (1,6,7).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the first report on the surgical excision of retrorectal tumours using single-incision robotic surgery with dVSP, which demonstrated its feasibility with favourable peri- were consistent with previous studies; however, the absence of intraoperative complications, specifically rectal injury, was noteworthy. 8,11,12 The selection of the surgical approach is conventionally dictated by the size and extent of the retrorectal tumour. Tumours extending beyond the S3 vertebral body or necessitating en bloc resection of adjacent organs warrant the adoption of an anterior or combined approach.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] There have been a few case series for robotic resection for retrorectal tumours especially in cases of tailgut cyst. [7][8][9][10] Rompen et al reported five cases of robotic resection for tailgut cysts situated at the S3-S5 level, posterior to the rectum, using the da Vinci Si system. They demonstrated the feasibility and safety of robotic resection, particularly emphasising the suitability of the robotic trans-abdominal approach when the cysts are located on the levator ani muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations